BIOMINERALIZATION OF MICROSTRUCTURAL VARIATIONS OF DENTINAL TUBULES AFTER ROOT CANAL OBTURATION USING MTA-BASED CEMENT WITH SUBSEQUENT SEM ANALYSIS - Dobrovolskyi, Dmytro; Gevkaliuk, Natallia (Eastern Ukrainian Medical Journal, 2026)
Introduction. The quality of endodontic treatment of teeth with intra-root resorption process directly depends on careful instrumental, medicinal treatment and root canal filling. The use of Mineral Trioxide Aggregate (MTA) cement aggregates during root canal obturation is of concern due to its bioactive interactions with dentinal tubule phosphoapatite. Methods. We prepared 50 curved root canals of human maxillary molars extracted according to indications and prepared them instrumentally for obturation. The intratubular biomineralization at the dentin-filling material interface was carefully analysed by scanning electron microscopy (SEM). Results.We prepared 50 curved root canals of human maxillary molars extracted according to indications and prepared them instrumentally for obturation. The intratubular biomineralization at the dentin-filling material interface was carefully analysed by scanning electron microscopy (SEM). In the case of root canal obturation with GP and MTA sealer, increased biomineralization of dentinal tubules outside the penetrating sealant mark was confirmed by SEM observation (p<0.05). Mineralised structures of phosphoapatite (calcium/phosphorus ratio 1.45-1.89) were detected on the path of MTA penetration through dentinal tubules at a distance of 350-400 µm from the tubule mouth. The beginnings of crystallisation were observed along the intra- and/or intertubular dentin collagen. The depth of intratubular biomineralization was significantly increased in all pretreated dentinal tubules (p<0.05). Conclusions. MTA cement and its derivatives can be used as a promising bioactive root canal filling agent to enhance biomineralization of dentinal tubules in a controlled environment.